Environmental factors influencing construction implementation from contractors’ perspective - Maelissa, Nelda; Prihartanto, Eko; Ratnasari, Anisa (Environmental and Toxicology Management, 2023)
To achieve the project’s goal, both internal and external organization influencing factors (construction industry) should be aware, particularly at the construction implementation level. The objective of this research is to identify the environmental factors that influence construction implementation from the contractor’s perspective as the main actors in the implementation of construction. The methodology used in this research was library research and surveys using questionnaires as data instruments. The analytical method used is principal component analysis, supported by the SPSS program. Based on the analysis results of the environmental factors that influence the construction implementation level using principle component analysis, the total class produced 15 main components and was capable of explaining the various data with a cumulative percentage of 85.672%. From the study results, it can be concluded that the company resource factor was the most influential factor compared with other factors.